2020
DOI: 10.1186/s40168-020-00920-y
|View full text |Cite
|
Sign up to set email alerts
|

β-glucan attenuates cognitive impairment via the gut-brain axis in diet-induced obese mice

Abstract: Background “Western” style dietary patterns are characterized by a high proportion of highly processed foods rich in fat and low in fiber. This diet pattern is associated with a myriad of metabolic dysfunctions, including neuroinflammation and cognitive impairment. β-glucan, the major soluble fiber in oat and barley grains, is fermented in the lower gastrointestinal tract, potentially impacting the microbial ecosystem and thus may improve elements of cognition and brain function via the gut-bra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
120
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(129 citation statements)
references
References 67 publications
8
120
1
Order By: Relevance
“…However, no significant difference was found in other inflammatory cytokines in the ileum and IL-6 and IL-10 level in serum. Although other studies reported that a long-term intake of oat β-glucan lowered the levels of inflammatory cytokines in the colon [ 42 ], we found no convincing evidence of an anti-inflammatory effect. Further studies are needed to investigate the anti-inflammatory effect of HGB flour.…”
Section: Discussioncontrasting
confidence: 99%
“…However, no significant difference was found in other inflammatory cytokines in the ileum and IL-6 and IL-10 level in serum. Although other studies reported that a long-term intake of oat β-glucan lowered the levels of inflammatory cytokines in the colon [ 42 ], we found no convincing evidence of an anti-inflammatory effect. Further studies are needed to investigate the anti-inflammatory effect of HGB flour.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, SCFAs also suppress the synthesis of the hunger-suppressing hormones leptin, peptide YY and glucagon-like peptide 1 43 . Consistent with a recent study 35 , propionate-induced activation of AKT was shown to be involved in regulating lipid accumulation by indirectly regulating Acc1 expression 17 , 18 and nutrient absorption-related gene transcription in a human FHC cell line (Figure 6 E). Consistently, the levels of Acc1 were increased in the WAT, liver and intestine (Figures 3 C, 3D and 4B).…”
Section: Discussionsupporting
confidence: 91%
“…Genomic DNA amplification and sequencing were performed as described in a previous study 17 . Briefly, total DNA was extracted from feces ( n = 3-5/group) using an E.Z.N.A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arabinoxylan plays an important role in maintaining the integrity of the gut by increasing the proliferation of goblet cells as well as secretion of IgA. β -glucan not only could improve metabolic condition, but also could attenuate cognitive impairment [ 7 , 8 , 9 ]. Glucomannan is helpful for bone metabolism and immunity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%